Stability studies of lincomycin hydrochloride in aqueous solution and intravenous infusion fluids - Czarniak, Petra; Boddy, M.; Sunderland, Bruce; Hughes, Jeff (Dove Medical Press Ltd., 2016)
Purpose: The purpose of this study was to evaluate the chemical stability of Lincocin® (lincomycin hydrochloride) in commonly used intravenous fluids at room temperature (25°C), at accelerated-degradation temperatures and in selected buffer solutions. Materials and methods: The stability of Lincocin® injection (containing lincomycin 600 mg/2 mL as the hydrochloride) stored at 25°C±0.1°C in sodium lactate (Hartmann’s), 0.9% sodium chloride, 5% glucose, and 10% glucose solutions was investigated over 31 days. Forced degradation of Lincocin® in hydrochloric acid, sodium hydroxide, and hydrogen peroxide was performed at 60°C. The effect of pH on the degradation rate of lincomycin hydrochloride stored at 80°C was determined. Results: Lincomycin hydrochloride was found to maintain its shelf life at 25°C in sodium lactate (Hartmann’s) solution, 0.9% sodium chloride solution, 5% glucose solution, and 10% glucose solution, with less than 5% lincomycin degradation occurring in all intravenous solutions over a 31-day period. Lincomycin hydrochloride showed less rapid degradation at 60°C in acid than in basic solution, but degraded rapidly in hydrogen peroxide. At all pH values tested, lincomycin followed first-order kinetics. It had the greatest stability near pH 4 when stored at 80°C (calculated shelf life of 4.59 days), and was least stable at pH 2 (calculated shelf life of 0.38 days). Conclusion: Lincocin® injection was chemically found to have a shelf life of at least 31 days at 25°C when added to sodium lactate (Hartmann’s) solution, 0.9% sodium chloride solution, 5% glucose solution, and 10% glucose solution. Solutions prepared at approximately pH 4 are likely to have optimum stability.